2009
DOI: 10.1126/scitranslmed.3000278
|View full text |Cite
|
Sign up to set email alerts
|

A Role for VAV1 in Experimental Autoimmune Encephalomyelitis and Multiple Sclerosis

Abstract: Multiple sclerosis, the most common cause of progressive neurological disability in young adults, is a chronic inflammatory disease. There is solid evidence for a genetic influence in multiple sclerosis, and deciphering the causative genes could reveal key pathways influencing the disease. A genome region on rat chromosome 9 regulates experimental autoimmune encephalomyelitis, a model for multiple sclerosis. Using interval-specific congenic rat lines and association of single-nucleotide polymorphisms with infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 52 publications
(86 reference statements)
4
47
0
Order By: Relevance
“…For example, crosses between the highly polymorphic DA and PVG. AV1 rat strains, which demonstrate differential susceptibilities to EAE, have led to successful identification of several candidate genes that have also been translated as MS risk genes, including MHCIITA, VAV1, IL-21R, and CCL chemokines (13,(15)(16)(17). Importantly, congenic lines can be established for risk genes and thereby offer a tool in further studying their functional relevance.…”
Section: Ultiple Sclerosis (Ms) Is a Demyelinating Inflammatorymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, crosses between the highly polymorphic DA and PVG. AV1 rat strains, which demonstrate differential susceptibilities to EAE, have led to successful identification of several candidate genes that have also been translated as MS risk genes, including MHCIITA, VAV1, IL-21R, and CCL chemokines (13,(15)(16)(17). Importantly, congenic lines can be established for risk genes and thereby offer a tool in further studying their functional relevance.…”
Section: Ultiple Sclerosis (Ms) Is a Demyelinating Inflammatorymentioning
confidence: 99%
“…A follow-up study was then performed using a Norwegian cohort including 548 patients (396 female patients) and 554 control subjects (323 female subjects) (15). All patients of the Norwegian cohorts gave written informed consent to participate.…”
Section: Human Association Studiesmentioning
confidence: 99%
“…Genetic risk factors indicate that the heritable risk of developing MS is associated with allelic variants of predominantly immune-related genes (3)(4)(5)(6)(7). The strongest association is conferred by the human leukocyte/Ag locus (8).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…In a paper published in Science Translational Medicine, a Karolinska team reported that increased levels of Vav 1 guanine nucleotide exchange factor (VAV1), a protein involved in T and B cell activation, are associated with MS. 2 Meanwhile, the University of Tokyo researchers identified microsomal prostaglandin E synthase-1 (PTGES; mPGES-1) as a target involved in the development of pathogenic T cells. That study was published in the Proceedings of the National Academy of Sciences.…”
Section: By Lauren Martz Staff Writermentioning
confidence: 99%
“…Recent studies have shown that dysfunctional T helper type 1 (TH1) and TH17 cells cause autoreactivity, which can prompt the immune system to attack the myelin sheath around neurons. 1 Thus, many groups are focused on identifying the pathways that lead to the aberrant T cell activation.In a paper published in Science Translational Medicine, a Karolinska team reported that increased levels of Vav 1 guanine nucleotide exchange factor (VAV1), a protein involved in T and B cell activation, are associated with MS. 2 Meanwhile, the University of Tokyo researchers identified microsomal prostaglandin E synthase-1 (PTGES; mPGES-1) as a target involved in the development of pathogenic T cells. That study was published in the Proceedings of the National Academy of Sciences.…”
mentioning
confidence: 99%